TRAININGS USAGE IN THE PROFESSIONAL EDUCATION OF FUTURE SOCIOCULTURAL ACTIVITY MANAGERS - Boyko, Olga; Jeremus-Lewandowska, Anna; Otroshchenko, Larysa; Povalii, Tatiana (Socio-Cultural Management Journal, 2020)
Introduction. The relevance of the socio-cultural field is growing now. There is a necessity of highlighting the innovative forms of future socio-cultural activity managers’ education, connected with manager activity content, dealing with keeping and sharing of cultural values management. Purpose and methods. The purpose of the article is theoretical analysis, systematization, and generalization of the scientific research concerning the justification of trainings usage peculiarities in future socio-cultural activity managers’ education. In the course of the research, such general scientific methods as analysis, synthesis, systematization, and generalization of theoretical issues have been used, as well as specific scientific methods of terminological, retrospective, systematic-structural, and structural-functional analysis. Results. Key moments in the history of trainings emergence and development have been highlighted. Kinds of trainings have been analysed: personal-oriented, skills-building, marketing, managerial, staff training, and organizational ones. The structure of trainings preparation in the professional education of future socio-cultural managers has been systematized, which is specified under the following indicators: stages, sections, aim, examples of implementation. Trainings content has been analysed and its illustrative subject matter has been presented. Teacher-trainer personal qualities have been distinguished, and his professional excellence elements have been detected. Conclusions. The scientific novelty of obtained results is in the concretization of the concept “training”, systematization of training preparation structure, and providing illustrative subject matter of trainings for future socio-cultural activity managers’ education; practical value is in the possibility of obtained results usage in the universities’ education process.